DISCOURSE ON KAFOAMPE IN THE TRADITIONAL MARRIAGE OF MUNA ETHNIC IN MUNA REGENCY, SOUTHEAST SULAWESI - Hasanah, Nurul; Suastika, I Made; Arsana, I Gusti Ketut Gde (E-Journal of Cultural Studies; Volume 11, Number 3, August 2018, 2018)
This study aims to reveal and understand about the discourse on kafoampe in the traditional marriage of Muna community in Muna Regency, Southeast Sulawesi Province. This is a qualitative research, which is categorized into cultural studies. The result of study shows, kafoampe symbolized by the amount of money given by the family of the bride to the family of the groom to be used to finance the marriage. Kafoampe is a form of appreciation of the groom's family to the family of the bride, which can be given either in the form of money as a whole or by including livestock, and other food items in accordance with the agreement of the two great families. In addition to being regarded as a form of awards, kafoampe also has a meaning to tighten the bond and strengthen the familial relationship between the two big families in a marriage as well as strengthening the familial relationship with the surrounding community.